Nur transcription factors in stress and addiction - Campos-Melo, Danae; Galleguillos, Danny; Sánchez, Natalia; Gysling, Katia; Andrés, María E. (Frontiers in Molecular Neuroscience, 2013)
The Nur transcription factors Nur77 (NGFI-B, NR4A1), Nurr1 (NR4A2) and Nor-1 (NR4A3) are a sub-family of orphan members of the nuclear receptor superfamily. These transcription factors are products of immediate early genes, whose expression is rapidly and transiently induced in the central nervous system by several types of stimuli. Nur factors are present throughout the hypothalamus-pituitary-adrenal axis where are prominently induced in response to stress. Drugs of abuse and stress also induce the expression of Nur factors in nuclei of the motivation/reward circuit of the brain, indicating their participation in the process of drug addiction and in non-hypothalamic responses to stress. Repeated use of addictive drugs and chronic stress induce long-lasting dysregulation of the brain motivation/reward circuit, due to reprogramming of gene expression and enduring alterations in neuronal function. Here, we review the data supporting that Nur transcription factors are key players in the molecular basis of the dysregulation of neuronal circuits involved in chronic stress and addiction.